3D printed facial laser scans for the production of localised radiotherapy treatment masks – A case study. (1st October 2016) - Briggs, Matthew; Clements, Helen; Wynne, Neil; Rennie, Allan; Kellett, Darren
Abstract: This study investigates the use of 3D printing for patients that require localised radiotherapy treatment to the face. The current process involves producing a lead mask in order to protect the healthy tissue from the effects of the radiotherapy. The mask is produced by applying a thermoplastic sheet to the patient's face and allowing to set hard. This can then be used as a mould to create a plaster impression of the patient's face. A sheet of lead is then hammered on to the plaster to create a bespoke fitted face mask. This process can be distressing for patients and can be problematic when the patient is required to remain motionless for a prolonged time while the thermoplastic sets. In this study, a 1:1 scale 3D print of a patient's face was generated using a laser scanner. The lead was hammered directly on to the surface of the 3D print in order to create a bespoke fitted treatment mask. This eliminated the thermoplastic moulding stage and significantly reduced the time needed for the patient to be in clinic. The higher definition impression of the the face resulted in a more accurate, better fitting treatment mask.